The Development of Sekrebel Application Based on Folklore For High School Students - Ayu Chandra Dewi; Sumarwati; Kenfitria Diah Wijayanti (Britain International for Academic Research (BIAR) Publisher, 2025)
The introduction of Javanese script to the younger generation, especially high school students, has become a challenge in today's digital era. Lack of interest and less interactive learning methods have led to low literacy in Javanese script. Therefore, this study aims to develop the